Nilobray Vidyalaya - Sharma, Rajeev (London : SAGE Publications Ltd, 2017)
The case is about a secondary school located in Ralegan Siddhi village in Ahmednagar district of Maharashtra state. The school has a policy of giving priority in admission to children who have either failed or have been expelled from other schools on the ground of indiscipline. Such children, who constitute about half of the population of the school, stay in a residential facility on campus and study with other children, who come from the nearby villages. The grade X and XII result of the school is comparable with other schools which admit children on the basis of merit. The case describes various activities and processes which are aimed at holistic development and values among children along with academics.
Originally published: Sharma, R. (2012). Nilobray Vidyalaya. RJMC0024. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Nilobray Vidyalaya; Rural schools -- India -- Ahmednagar -- Case studies; Education, Secondary -- India -- Ahmadnagar -- Case studies; Education, Rural -- Social aspects -- India -- Ahmadnagar -- Case studies